Computational Thinking Analysis In Elementary School - Sakinah, Ainur; Herman, Tatang (International Conference on Elementary Education, 2025)
This study aims to determine how students apply computational thinking indicators in solving comparison problems. The method applied in this study is a descriptive qualitative approach involving four students as research subjects, where the four students were selected randomly. Each student is given one problem. This means that each student faces challenges in the form of different problems, but remains within the same context. This study was conducted on fifth grade students of SD Negeri 1 Panorama, Hegarmanah Village. The results of this test will be used to assess students' computational thinking skills in solving mathematical problems. In the decomposition indicator, students are generally able to break down problems into smaller parts, such as determining the elements that must be compared (the number of bottles of juice and mineral water). In the pattern recognition indicator, students are quite good at recognizing relationships or patterns between elements, such as ratios in comparisons, while the abstraction indicator is the biggest challenge for students, especially in filtering important information and ignoring irrelevant details. In addition, in the algorithm design indicator, some students still have difficulty designing systematic steps to simplify comparisons to their simplest form. Overall, students need a more structured learning approach that supports the development of CT skills, especially in abstraction and algorithm design, to improve their understanding of the comparison material. Therefore, it can be concluded that students have applied the four computational thinking indicators. Although there are still mistakes made by students in solving math problems, students have been able to apply the four foundations of computational thinking.